2022
DOI: 10.2147/ppa.s357580
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver Burden Among Informal Caregivers of Persons Living with HIV/AIDS in Liangshan Prefecture, China

Abstract: Purpose Previous studies revealed that informal caregivers for persons living with HIV/AIDS (PLWHA) experience perceived caregiver burden. Although Liangshan prefecture is one of the areas with the fastest growing HIV/AIDS epidemics in China, little is known about burden of informal caregivers for PLWHA. This study aimed to evaluate caregiver burden and these predictors among informal caregivers of PLWHA in Liangshan prefecture, China. Methods This was a cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…For instance, a cross-sectional study conducted in the Liangshan Yi region of China revealed that most caregivers experienced a heavy burden, with older caregivers and those in poor health facing greater burdens. 39 In the Udagan region, most family caregivers reported a mild to moderate burden. 40 In contrast to our findings, a study conducted in Thailand reported a relatively low caregiver burden.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a cross-sectional study conducted in the Liangshan Yi region of China revealed that most caregivers experienced a heavy burden, with older caregivers and those in poor health facing greater burdens. 39 In the Udagan region, most family caregivers reported a mild to moderate burden. 40 In contrast to our findings, a study conducted in Thailand reported a relatively low caregiver burden.…”
Section: Discussionmentioning
confidence: 99%
“…13 Therefore, it is necessary to investigate the real experience and feelings of informal caregivers of PLWHA. But in China most of the current researches on care experience of informal caregivers of PLWHA are quantitative in nature, 7,14 which may appear insufficient for understanding informal caregivers' lived experiences and perceptions. However, a qualitative approach would provide a more nuanced understanding of the caregivers' perspectives.…”
Section: Introductionmentioning
confidence: 99%